National Industrial Training Authority - Government of Kenya
The National Industrial Training Authority (NITA) is a state corporation established under the Industrial Training (Amendment) Act of 2011. The Authority has five industrial training centres spread across the country.
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; Industrial Training Institutes; publicImportV1